Unraveling Millennial Online Shopping Preferences: A Comprehensive Analysis of Factors Influencing Consumer Behaviour in the Digital Marketplace - Kalariya, Kush; Chauhan, Rahul; Soni, Parth; Patel, Mohit; Patel, Himalay (Journal of Business and Halal Industry, 2024)
The study explores millennial preferences in online shopping by examining the influence of various factors on consumer behaviour in the digital marketplace. Through a comprehensive statistical analysis, significant relationships between constructs such as cultural influence, marketing strategies, social factors, and online purchasing behaviour were identified. The findings highlight the importance of understanding consumer motivations and preferences in shaping effective marketing strategies targeted at millennial consumers. While factors like cultural and social influences were found to significantly affect consumer behaviour, the direct influence of marketing strategies and personal characteristics on online purchasing decisions was less pronounced. The study underscores the complexity of millennial shopping behaviour and emphasizes the need for businesses to consider a holistic approach when designing marketing campaigns and interventions. By understanding, the interplay of factors influencing millennial preferences in online shopping, marketers can develop more targeted and effective strategies to engage this key demographic in the digital marketplace.